The Influence of Transformational Leadership and Motivation on Innovative Work Behavior at PT PLN (Persero) UP2B Sistem Minahasa - Legi, Angelina Pingkan; Tatimu, Ventje; Rumawas, wehelmina (Productivity, 2024)
The aim of this research is to determine the influence of transformational leadership and motivation on innovative work behavior at PT PLN (Persero) UP2B Minahasa System. This research uses quantitative research methods. The population in this study were all employees of PT PLN (Persero) UP2B Minahasa System, totaling 36 people. The data collection technique in this research uses a questionnaire technique. The data analysis technique in this research uses Path Analysis, Partial Least Square (PLS) and Hypothesis Testing. Data processing in this research used the SmartPLS 4 software program. From the research results it can be concluded that the results of the first hypothesis test show that the relationship between transformational leadership variables and innovative work behavior has a correlation value of 0.281. The results of the second hypothesis test show that the relationship between motivation variables and innovative work behavior has a correlation value of 0.524. Based on the calculation results, it shows that transformational leadership and motivation have a positive effect on innovative work behavior. This is proven by the R Square value of 0.596. This shows that the higher the transformational leadership and motivation, the better the influence on innovative work behavior. Keywords: Transformational Leadership, Motivation, and Innovative Work Behavior